2016
DOI: 10.1002/ccd.26594
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two different renal denervation strategies on blood pressure in resistant hypertension: Comparison of full‐length versus proximal renal artery ablation

Abstract: The results indicate that proximal RDN has a similar efficacy and safety profile compared with full-length RDN, and propose the proximal artery as the key portion for RDN. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In an experimental porcine model, similar results were obtained . These results were not confirmed in a single human study which compared BP‐lowering efficacy between proximal and full‐length artery energy delivery . There are technical limitations with this study; the primary endpoint was office blood pressure and the mean number of ablations was only 6 and 3 in each artery for full‐length and proximal denervation, respectively.…”
Section: Methodsmentioning
confidence: 64%
“…In an experimental porcine model, similar results were obtained . These results were not confirmed in a single human study which compared BP‐lowering efficacy between proximal and full‐length artery energy delivery . There are technical limitations with this study; the primary endpoint was office blood pressure and the mean number of ablations was only 6 and 3 in each artery for full‐length and proximal denervation, respectively.…”
Section: Methodsmentioning
confidence: 64%
“…In addition, animal experimental studies conducted by Lu et al [43] and Yu et al [47] have indicated that the sites of BP elevation by electrical stimulation of the renal artery tend to be distributed primarily in the proximal and middle segments of the renal artery rather than in the distal segment of the renal artery. Similarly to previous animal studies, the clinical study by Chen et al [48] has indicated that proximal RDN has a similar efficacy and safety profile to that of full-length RDN; the authors have proposed that the proximal artery is the key target portion for RDN. In addition, Konstantinos et al [49] used the ConfidenHT system to perform simple renal artery electrical stimulation in 20 patients with hypertension in 2018.…”
Section: Renal Nerve Electrical Stimulation-guided Rdnmentioning
confidence: 71%
“…In line with this finding, ablation at the main renal artery branch and at the distal branches showed greater norepinephrine reduction than performing proximal ablation alone . In this issue of the Journal, Chen and coworkers report a randomized comparison of these two RD strategies in Chinese individuals with severe hypertension (systolic and diastolic blood pressure values were 179–182 mm Hg and 103–104 mm Hg, respectively). The authors found a similar antihypertensive effect in both groups, despite a longer radiofrequency time in the full‐length ablation group.…”
mentioning
confidence: 82%